Податкові хайпи-2018 - Швабій, Костянтин Іванович (Зеркало недели, 2018)
Досліджено податкові хайпи різного штибу в Україні. Виявлено причин цих явищ, де головна з них породжена впливом політичних чинників, зокрема, наближенням череди виборів. Показано технологію маніпулювання суспільною думкою на користь можновладців.

The tax hippies of different types in Ukraine are investigated. The causes of these phenomena are revealed, where the main of them is generated by the influence of political factors, in particular, approaching the election chamber. The technique of manipulating public opinion in its favor is shown.
Keywords: податкова служба; ДФС; митна служба; держава; BEPS; економічна діяльність; Tax Service; SFS; Customs; State; BEPS; Economic Activities